USER’S PERCEPTIONS OF SACREDNESS (Case Study: Catholic Churches in Indonesia) - Nita Dwi Estika; Hanson E. Kusuma; Angela Christysonia Tampubolon; Filipus Bagus Widyawan (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2021)
Sacredness in Catholic churches has two aspects: sacredness derived from the purpose and activities of worship and sacredness that arises from the physical and spatial aspects of a church building. The purpose of this study was to reveal factors that affect sacredness in Catholic churches from the perspective of the worshiper. The researchers conducted an exploratory qualitative research to collect text data related to the perception of Catholic church sacredness. The data were collected through an online questionnaire. The researchers also conducted an explanatory quantitative research to uncover the relationship between level of church sacredness and physical and nonphysical factors. The results showed that the ‘sacred spirit’ factor tends to be more dominant in affecting church sacredness compared to ‘sacred object’. Worshipers measure church sacredness according to ‘devoted reflection’, ‘relationship with God’, ‘quality of space’, ‘enclosure acculturation’, and ‘building style’.